Analisis Terhadap Pelaksanaan Putusan (Eksekusi) Perkara Perdata - Phireri; Muhammad Sabir Rahman; Delvi Paluaran; Andi Fauzan Makmur (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2022)
The purpose of writing this article is to determine how to implement civil case decisions that have permanent legal force (in Kracht van gewijsde). And non-judicial and juridical obstacles can occur during the implementation of case decisions. The method used in this writing is a normative legal research method using an analytical approach by analyzing legal principles, legal principles, and the existing legal system in laws and regulations. It is supported by secondary data from research and scientific results. The results of the study show that the procedures for implementing civil case decisions that have legal force are still carried out by district courts which in practice often encounter several obstacles, such as juridical obstacles in the form of PK or judicial review submitted by the respondent for execution to the Supreme Court and the presence of Derden Verzet submitted by a third party. as resistance put forward before execution. And non-juridical obstacles such as changing hands of the object of execution or the object of execution no longer belonging to the death row convict. And as prevention of obstacles that will occur, the District Court can ask for assistance from law enforcement officials such as the TNI and Polri so that the execution procedure in its implementation can run smoothly and no one obstructs the execution process.